WATER QUALITY AND ITS EFFECT ON GROWTH AND SURVIVAL RATE OF LOBSTER REARED IN FLOATING NET CAGE IN EKAS BAY, WEST NUSA TENGGARA PROVINCE - Muhammad Junaidi; Mat Sardi Hamzah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT The development of lobster farming in floating net cage in Ekas Bay caused an environmental degradation such as decrease water quality due to some aquaculture wastes. The purposes of this study were to determine the status of water quality and their effect on growth and survival rate of lobster reared in floating net cages (FNC) in the Ekas Bay, West Nusa Tenggara Province. Water sample collection and handling referred to the APHA (1992). Analyses of water quality data were conducted using Principal Component Analysis. Determination of the water quality status of Ekas Bay was performed with STORET system. Multivariate analyses were used to determine the relationship between water quality, growth, and survival rate of lobster reared in FNC. Results showed that Ekas Bay water quality status was categorized in class C (medium contaminated), which exceeded some quality standard parameters such as ammonia (0.3 mg/l), nitrate (0.008 mg/l), and phosphate (0.015 mg/l). During lobster farming activities feeding with trash fish for 270 days, we obtained daily growth rate of  0.74% (lower than normal growth rate of 0.86%), survival rate of 66% (lower than normal survival rate of 86.7%), and feed conversion ratio of 11.15. Ammonia was found as a dominant factor reducing growth  and survival rate of lobster reared in FNC. Keywords: water quality, lobsters, growth, survival, Ekas Bay